Comparison of Catecholamine Values Before and After Exercise-Induced Bronchospasm in Professional Cyclists - Messan, Folly; Tito, Albérick; GOUTHON, N. M. POLYCARPE; BIO NIGAN, ISSIAKO; Blagbo, Sewanou Abel (My University, 2017)
Background: The concentration of circulating catecholamine increases during exercise in healthy athletes, but the variation has not been studied much in athletes who develop exercise-induced bronchospasm. This study measured changes in circulating catecholamine levels using the induced maximal effort test in the laboratory in professional cyclists sensitive to bronchospasm. Materials and Methods: This experimental study included 86 professional cyclists. They underwent two pulmonary function tests (to determine forced expiratory volume in one second [FEV1]) and two blood samples (to measure adrenaline and noradrenaline levels) were drawn before and after the stress test. Two subsets emerged: subjects whose FEV1 decreased by at least 10% from the resting value and non-sensitive subjects whose FEV1 do not meet this criterion. Results: A total of 51 cyclists (59%) were classified into the sensitive group. Resting catecholamine levels showed no significant difference (p > 0.05) between the two groups. In contrast, at the end of the exercise test, the adrenaline (581.9 ± 321.0 pg/mL versus 1783.5 ± 1001.0 pg/mL) and noradrenaline (4994.0 ± 2373.0 pg/mL versus 3205.0 ± 7714.4 pg/mL) levels were both lower in the sensitive group than those in the resting group (p < 0.0001). Conclusion: The frequency of the occurrence of bronchospasm observed in the studied cyclists was one of the highest among professional sports environments and the circulating catecholamine level was low in cyclists susceptible to bronchospasm. A training protocol adapted to their respiratory physiological profile may be indicated.
Keywords: Adrenaline; Noradrenaline; Bronchospasm; Prevalence; Lung function; Cyclists